Etiology And Occurrence Of Valsa Apple Canker In Jammu & Kashmir State (Applied Biological Research, 2011)
Apple (Malus domestica Borkh.), a predominant fruit crop of Jammu & Kashmir State, is grown on an  area of 1,19,041 ha and contributes towards 65% of the total fruit produce of the State (Anonymous,  2008). In recent years apple trees have encountered a new problem in the form of various types of  cankers which have assumed epiphytotic proportions in some pockets of Kashmir valley (Bhat et al.,  2009). The cankers inflict huge economic losses through girdling of limbs and branches, blightening  and die-back of twigs and ultimately lead to the death of either whole or part of the tree (Jones and  Aldwinkle, 1990). In view of the alarming damage by canker diseases on apple trees, a preliminary  study was undertaken to assess the canker status in Kashmir valley and to identify the causal pathogen.
Keywords: Etiology; Occurrence; Kashmir